CURRICULUM METAPHORS - IBRAHİM, Amr Moneer (The Eurasia Proceedings of Educational and Social Sciences, 2016)
One Of The Most Common Learning Tools In The Subject Domain Of Education Is Metaphors. It Has Been Said That Learning Is Not Possible Without Metaphors, Let Alone The Usage Of Metaphors In Our Daily Routine Without Even Noticing. A Lot Of Our Common Speech Is Full With Metaphors That Became A Part Of Our Normal Dialogue, To The Extent That We Do Not Consider The “Figure Of Speech” A Metaphor Any Longer. More importantly, using metaphors to describe curriculum has been a method adopted by scholars trying to “practicalaise” curriculum and give it a living-like sense. Eventually, curriculum metaphors took a steep turn (in some cases) when it started navigating educational policies to undesirable areas of application. From that perspective, this paper will analyse the favourable/unfavourable effects of curriculum metaphors in general, with addition to an in-depth investigation of the appropriateness, the reliability and validity of notions of Production, Growth, and Journey as curriculum metaphors; explored in a short (but highly influential) article by Herbert Kliebard in 1972, and since, literature has been deliberating and confronting these three metaphors (among others like Medicine or Natural Resources) for their ability in characterizing curriculum.